Effect of Project-Based Learning and Communication Skills On Students' Reasoning Ability - Ariyani Muljo; I Nyoman Sudana Degeng; Cholis Sadijah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
This study aims to investigate the impact of communication skills and the project-based learning (PBL) model on the reasoning skills of eighth-grade students at SMP Islam Nurul Huda. This study used a two-group experimental design, with one experimental group using the PjBL model and the other group using traditional techniques. A two-way MANOVA approach was used in analysing the data. The results showed that the PjBL model significantly improved students' abilities in mathematical reasoning and problem solving compared to the traditional approach. The learning model and communication ability interacted to affect reasoning ability, but there was no difference in ability based on students' communication ability level.